2011
DOI: 10.3892/mmr.2011.441
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms of BTN2A1 and ILF3 with myocardial infarction in Japanese individuals with different lipid profiles

Abstract: Abstract. dyslipidemia is an important risk factor for myocardial infarction (Mi). We previously showed that gene polymorphisms associated with Mi differed among individuals with different lipid profiles. We also showed that rs6929846 of BTN2A1 and rs2569512 of ILF3 were significantly associated with MI in Japanese individuals. in the present study, we examined the relationship between rs6929846 of BTN2A1 or rs2569512 of ILF3 and Mi in individuals with low or high serum concentrations of triglycerides, high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For example, upon suppression of BUD13 and ILF3, we observed a downregulation of target miR-144. BUD13is an RBP with putative roles in splicing (Dziem- bowski et al, 2004) that has been associated with metabolic syndrome (Lin et al, 2016), while ILF3 has a putative role in cardiovascular disease (Yoshida et al, 2011a, 2011b) and was previously shown to interact with DGCR8 (Shiohama et al, 2007). We found that these RBPs affect the miR-144 locus, mostly likely by promoting stability of the precursor (ILF3, which has a binding site within the pre-miR) or the primary (BUD13, which has a pre/ pri-junction spanning cluster) miRNA transcript.…”
Section: Discussionmentioning
confidence: 99%
“…For example, upon suppression of BUD13 and ILF3, we observed a downregulation of target miR-144. BUD13is an RBP with putative roles in splicing (Dziem- bowski et al, 2004) that has been associated with metabolic syndrome (Lin et al, 2016), while ILF3 has a putative role in cardiovascular disease (Yoshida et al, 2011a, 2011b) and was previously shown to interact with DGCR8 (Shiohama et al, 2007). We found that these RBPs affect the miR-144 locus, mostly likely by promoting stability of the precursor (ILF3, which has a binding site within the pre-miR) or the primary (BUD13, which has a pre/ pri-junction spanning cluster) miRNA transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that ILF3 plays a novel and central role in angiogenesis [39]. Tetsuro et al reported that rs2569512 of ILF3 were signi cantly associated with myocardial infarction (MI) in Japanese individuals [40]. The study of ILF3 polymorphism in tumors has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%